Epidemic of Pseudomonas cepacia in an adult cystic fibrosis unit: evidence of person-to-person transmission. - Smith, D L (1993)
An epidemic of Pseudomonas cepacia occurred in an adult cystic fibrosis center in the United Kingdom, despite a policy of segregation of infected and noninfected patients within the hospital. Investigation of the outbreak by ribotyping and pulsed-field gel electrophoresis to characterize P. cepacia strain genomes together with inquiry into social contacts between patients revealed evidence of person-to-person transmission outside the hospital environment. Segregation policies aimed at reducing the spread of this infection in the cystic fibrosis community need to encompass patient contacts outside the hospital environment.